2011
DOI: 10.4103/0028-3886.79144
|View full text |Cite
|
Sign up to set email alerts
|

Poor-grade subarachnoid hemorrhage: Is surgical clipping worthwhile?

Abstract: With an aggressive approach aimed at early clipping, the chances of rebleed are reduced and vasospasm can be managed more aggressively. This protocol resulted in survival in a significant proportion of patients who would have otherwise died. In the long-term follow-up, the surviving patients showed significant improvement from the status at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
(69 reference statements)
0
20
0
1
Order By: Relevance
“…[1] Mortality reported with aneurysmal SAH (aSAH) is about 50% and furthermore, survivors of aSAH are left with high morbidity. [3,4] aSAH also pose risk for hypothalamo-pituitary dysfunctions as a result of proximity of hypothalmo-pituitary structure to the circle of Willis. Over the last few years, number of studies has been carried out to determine hypothalamo-pituitary dysfunction in survivor of aSAH.…”
Section: Endocrine Abnormalities Definitionsmentioning
confidence: 98%
“…[1] Mortality reported with aneurysmal SAH (aSAH) is about 50% and furthermore, survivors of aSAH are left with high morbidity. [3,4] aSAH also pose risk for hypothalamo-pituitary dysfunctions as a result of proximity of hypothalmo-pituitary structure to the circle of Willis. Over the last few years, number of studies has been carried out to determine hypothalamo-pituitary dysfunction in survivor of aSAH.…”
Section: Endocrine Abnormalities Definitionsmentioning
confidence: 98%
“…In thousands of hundreds patients with aSAH, the poor-grade cases takes the proportion from 24% to 45%, and the clinical outcome of this population remains dismal (15). It is also reported that the re-bleeding rate is actually higher compared with good-grade (15).…”
Section: Poor Clinical Condition At Admissionmentioning
confidence: 99%
“…Early surgery should be carried out as soon as the patient's condition allows. In fact, a recent study (5) has determined that early intervention reduces re-bleeding and control vasospasm, thus significantly improving a patient's long-term survival. Early treatment of an aneurysm is the most effective means to prevent re-bleeding and "triple-H" (hypertension, hypervolemia, and hemodilution).…”
Section: Tan H Et Al: Surgical Timing Of Aneurysms With Acute Hydrocmentioning
confidence: 99%